Social Media Influence on Students' Knowledge Sharing and Learning: An Empirical Study - Arunkumar Sivakumar; Sudarsan Jayasingh; Shahenaz Shaik (MDPI AG, 2023)
Social media brought new opportunities not only for entertainment and marketing but also for knowledge sharing and learning. This research attempted to examine the effectiveness of social media as an educational tool and its impact on knowledge sharing among college and university students. The study used social cognitive and connective theories to develop a model that examines the influence of personal motivations (such as reputation) and social networking features (such as file sharing and student engagement) on information sharing. The study concluded that social media can promote knowledge sharing and can increase student motivation and performance. The findings suggest that social networking is a valuable method of information dissemination and can be used to encourage student engagement. The article also provides implications, restrictions, and future research directions for using social media in education. This study provides valuable insights for educators and institutions looking to incorporate social media into their teaching and learning strategies.